SEVERITY OF HEAD TRAUMA IN ROAD TRAFFIC ACCIDENT PATIENTS AT HAYATABAD MEDICAL COMPLEX HOSPITAL, PESHAWAR (The Research of Medical Science Review, 2025)
Background: Trauma has increasingly been recognized as a significant public health concern in developing countries, often termed a "silent plague" due to its high prevalence and low levels of public awareness. Among various types of trauma, traumatic brain injuries (TBIs) are particularly alarming, as they contribute substantially to morbidity and mortality rates in low- and middle-income nations. Methods: This Quantitative Cross Sectional research study of 361 patients investigates the epidemiology, injury patterns, and management outcomes of head trauma sustained in road traffic accidents (RTAs). Imaging studies revealed that 89.2% underwent CT or MRI scans to assess injury extent. Injury mechanisms showed 28.3% were pedestrians, while 71.7% were injured under other circumstances. The majority (70.4%) of patients were male. Results: The results show varied injury types, including depressed (18.3%), linear (28%), non-depressed (19.7%), stellate (10.5%), and other fractures (23.5%). Loss of consciousness occurred in 59.6% of patients, with 65.1% experiencing mild duration. Glasgow Coma Scale scores indicated 37.7% mild, 32.7% moderate, and 29.6% severe head injuries. Imaging detected intracranial haemorrhage in 24.7% of patients, with 25.2% requiring intervention for raised intracranial pressure. Surgical intervention was required in 37.1% of cases, with craniotomy (11.9%) and craniotomy (9.1%) being most common. Male patients (70.4%) and pedestrians (28.3%) were disproportionately represented. Management strategies included observation (50.4%), medical therapy (19.9%), and surgical intervention (29.6%). Conclusion: This study highlights the high burden of traumatic brain injuries (TBIs) from road traffic accidents, predominantly affecting males and pedestrians. The findings emphasize the need for prompt imaging, tailored interventions, and improved road safety measures to enhance patient outcomes and reduce the impact of TBIs in low- and middle-income countries.